Bridging Personality and Online Prosocial Behavior: The Roles of Empathy, Moral Identity, and Social Self-Efficacy - Leng, Jie; Guo, Qingke; Ma, Bingqing; Zhang, Shuyue; Sun, Peng (Frontiers in Psychology, 2020)
Personality has been considered as important influential factors of prosocial behavior (PB). This study aims to investigate whether the personality-PB association revealed in the real world is applicable to cyberspace. Researchers further considered moral identity, empathy, and social self-efficacy as mediators accounting for the association of personality and online prosocial behavior (OPB). Self-reported measures were administrated to 1398 participants from eastern China. Results showed (1) extraversion, agreeableness, conscientiousness, and openness were positively related to OPB, while neuroticism was negatively related to OPB; (2) perspective taking could serve as a mediator between all big five traits and OPB, social self-efficacy did the same job unless the predictor was agreeableness, and empathic concern and moral identity were less important mediators partly because OPB involves no face-to-face interaction. These findings show that personality has a significant effect on OPB through its influence on moral development.